2013
DOI: 10.1016/j.cell.2013.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Modulate Behavioral and Physiological Abnormalities Associated with Neurodevelopmental Disorders

Abstract: SUMMARY Although autism spectrum disorder (ASD) is defined by core behavioral impairments, gastrointestinal (GI) symptoms are commonly reported. Subsets of ASD individuals display dysbiosis of the gut microbiota, and some exhibit increased intestinal permeability. Here we demonstrate GI barrier defects and microbiota alterations in a mouse model displaying features of ASD, maternal immune activation (MIA). Oral treatment of MIA offspring with the human commensal Bacteroides fragilis corrects gut permeability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

60
2,273
5
21

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 2,692 publications
(2,440 citation statements)
references
References 98 publications
60
2,273
5
21
Order By: Relevance
“…Although ASD is a neurodevelopmental disorder, there are several comorbidities, such as gastrointestinal distress and immune dysregulation, observed in patients with ASD 43. Moreover, a gut‐microbiome‐brain connection was found to contribute to ASD pathogenesis,16 further suggesting that ASD is a systemic disorder caused by both genetic and environmental factors. In this regard, peripheral blood samples have been used to identify pathophysiology and biomarker of ASD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although ASD is a neurodevelopmental disorder, there are several comorbidities, such as gastrointestinal distress and immune dysregulation, observed in patients with ASD 43. Moreover, a gut‐microbiome‐brain connection was found to contribute to ASD pathogenesis,16 further suggesting that ASD is a systemic disorder caused by both genetic and environmental factors. In this regard, peripheral blood samples have been used to identify pathophysiology and biomarker of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…To generate the MIA model, pregnant C57BL6 mice were given intraperitoneal injections of 20 mg/kg of poly(I:C) (P9582, Sigma‐Aldrich, St. Louis, MO) on embryonic day 12.5 (E12.5), according to methods previously described 14, 16. Poly(I:C) lyophilized powder was reconstituted in nuclease‐free distilled water (10 mg/mL) to yield Poly(I:C) in an isotonic buffer solution, according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence has shown that the action of microbial metabolites can be a link between external factors and central nervous system function and behaviour (Cryan & Dinan, 2012; Hsiao et al., 2013). However, the exact mechanisms underlying how microbial metabolites regulate brain function have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous ‘axes’ were defined that link the gut with the lung, the skin and the brain and the gut microbiota is frequently considered as an important transducer of effects. Disturbances in the gut microbiota were, for example, reported to affect via a ‘gut–brain axis’ blood glucose homeostasis (De Vadder et al ., 2014) and even behavioural conditions like autism (Hsiao et al ., 2013). …”
Section: A Better Definition Of Biome Dysbiosismentioning
confidence: 99%